Design and fabrication of a stent for organ expansion surgery via 3D printing - Wong, Sheryl Yong Ling (Nanyang Technological University, 2024)
Vaginal agenesis and stenosis are two considerably niche conditions with the former only affecting about 1 in 4,500 to 5,000 females. Patients diagnosed with such a condition face discomfort and could possibly lead to complications such as impact on sexual relationships, inability to get pregnant, and other associated congenital anomalies. Considering the small proportion of people affected by it, the treatment options are likewise limited due to a low demand for proper devices. This is especially prevalent in countries with a small population, like Singapore, whereby we are now experiencing a lack of supply for the required devices due to the small number of patients. This leads to the use of modified over-the-counter solutions which may not necessarily be comfortable for patients. This report aims to alleviate such supply chain problems by evaluating the use of a 3D printed stent/device, providing a low-cost, customisable, and on-demand solution. With the aid of a medical expert from KKH, multiple designs were considered to incorporate a safe, comfortable design for use. Material considerations allowed this work to thoroughly evaluate possible materials that could be used by said staff. This work thus managed to produce a prototype which the author hopes will act as a stepping stone towards the commercialisation of such devices. This could potentially revolutionise the industry by providing personalised, affordable, and readily available solutions for niche medical conditions, thereby enhancing patient care, and improving quality of life. Future work includes exploring additional materials like medical-grade silicone and investigating the integration of inflatable features. This project demonstrates the potential of 3D printing for creating personalised vaginal stents, potentially improving patient comfort and treatment outcomes.